(untitled) (ENTHYMEMA, 2017)
This paper analyses and compares the variety of text types in the first verse translations of Dante’s Commedia: the Catalan translation by Andreu Febrer (1429), the Spanish translation by Pedro Fernández de Villegas (printed in 1515), and an anonymous French translation preserved in a manuscript dating from between 1491 and 1530. All these translations are the first verse translations of the work into their respective languages.